Ultra-low CONtraSt PCI vs conVEntional PCI in patients of ACS with increased risk of CI-AKI (CONSaVE-AKI) - Abhinav Shrivastava; Ranjit Kumar Nath; Himansu Sekhar Mahapatra; Bhagya Narayan Pandit; Ajay Raj; Ajay Kumar Sharma; Tarun Kumar; Dheerendra Kuber; Puneet Aggarwal (Indian Heart Journal, 2022)
Objectives: This prospective, randomized study assessed short-term outcomes and safety of ultra-low contrast percutaneous coronary intervention(ULC-PCI) vs conventional PCI in high risk for contrast induced acute kidney injury(CI-AKI) patients presenting with acute coronary syndrome(ACS). Background: Patients at an increased risk of developing CI-AKI can be identified prior to PCI based on their pre-procedural risk scores. ULC-PCI is a novel contrast conservation strategy in such high risk patients for prevention of CI-AKI. Methods: 82 patients undergoing PCI for ACS were enrolled having estimated glomerular filtration rate(eGFR) < 60 ml/min/1.73 m2 and moderate to very high pre-procedural risk of developing CI-AKI as calculated by Maioli risk calculator. They were randomized into two groups of 41 patients each of ULC-PCI (contrast volume ≤ patient's eGFR) and conventional PCI (contrast volume ≤ 3xpatient's eGFR). Primary end point was development of CI-AKI. Results: Baseline clinical and angiographic characteristics were similar between groups. Primary outcome of CI-AKI occurred more in patients of the conventional PCI group [7 (17.1%)] than in the ULC PCI group [(0 patients), p = 0.012]. Contrast volume (41.02 (±9.8) ml vs 112.54 (±25.18) ml; P < 0.0001) was markedly lower in the ULC-PCI group. No significant difference in secondary safety outcomes between two study arms at 30 days. IVUS was used in 17% patients in ULC PCI. Conclusion: ULC-PCI in patients with increased risk of developing CI-AKI is feasible, appears safe, and has the potential to decrease the incidence of CI-AKI specially in resource limited setting such as ours where coronary imaging by IVUS is not possible in every patient.